Web application design handbook : best practices for web-based software - Fowler, Susan L.; Stanwick, Victor R. (The Morgan Kaufmann series in interactive technologies, 2004)
The standards for usability and interaction design for Web sites and software are well known. While not everyone uses those standards, or uses them correctly, there is a large body of knowledge, best practice, and proven results in those fields, and a good education system for teaching professionals "how to." For the newer field of Web application design, however, designers are forced to reuse the old rules on a new platform. This book provides a roadmap that will allow readers to put complete working applications on the Web, display the results of a process that is running elsewhere, and update a database on a remote server using an Internet rather than a network connection. Web Application Design Handbook describes the essential widgets and development tools that will the lead to the right design solutions for your Web application. Written by designers who have made significant contributions to Web-based application design, it delivers a thorough treatment of the subject for many different kinds of applications, and provides quick reference for designers looking for some fast design solutions and opportunities to enhance the Web application experience. This book adds flavor to the standard Web design genre by juxtaposing Web design with programming for the Web and covers design solutions and concepts, such as intelligent generalization, to help software teams successfully switch from one interface to another. * The first interaction design book that focuses exclusively on Web applications.* Full-color figures throughout the book.* Serves as a "cheat sheet" or "fake book" for designers: a handy reference for standards, rules of thumb, and tricks of the trade.* Applicable to new Web-based applications and for porting existing desktop applications to Web browsers.